Managing Character Education for Students with Disabilities in Inclusive Elementary Schools - Hidayatis Sabila; Lailatussaadah (Al-Qalam Institue, 2026)
This study aims to analyze the management of character education for students with disabilities in inclusive elementary schools, with a focus on the application of planning, organizing, implementing, and evaluating functions. The study employed a qualitative descriptive approach. Data were collected through semi-structured interviews, non-participant observation, and document analysis involving school leaders and classroom teachers. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that character education management is implemented through an integrated yet gradual application of the POAC framework. Inclusive planning emphasizes core character values such as religiosity, empathy, tolerance, responsibility, and discipline, although these values are not yet supported by formal written documentation. Organizing is conducted flexibly through role distribution among school personnel, while implementation relies on role modeling, habituation, and adaptive daily learning activities. Evaluation focuses primarily on observing individual behavioral changes through informal communication with parents. The study implies that strengthening written planning and structured evaluation mechanisms is essential to enhance the sustainability and effectiveness of character education management for students with disabilities in inclusive school settings.